2012
DOI: 10.1001/archgenpsychiatry.2011.129
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial to Evaluate the Efficacy of Cognitive Therapy for Low-Functioning Patients With Schizophrenia

Abstract: Cognitive therapy can be successful in promoting clinically meaningful improvements in functional outcome, motivation, and positive symptoms in low-functioning patients with significant cognitive impairment. Trial Registration  clinicaltrials.gov Identifier: NCT00350883.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
226
4
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(249 citation statements)
references
References 41 publications
11
226
4
7
Order By: Relevance
“…There is some evidence suggesting that cognitive behavioral therapy focused on negative symptoms is effective in schizophrenic patients without 22q11.2DS (Klingberg et al, 2011;Perivoliotis & Cather, 2009). Interestingly, a recently published article showed that this type of intervention improved motivation in low-functioning patients with schizophrenia (Grant et al, 2012). This may indicate that similar strategies could be implemented in patients with 22q11.2DS to improve negative symptoms.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 96%
“…There is some evidence suggesting that cognitive behavioral therapy focused on negative symptoms is effective in schizophrenic patients without 22q11.2DS (Klingberg et al, 2011;Perivoliotis & Cather, 2009). Interestingly, a recently published article showed that this type of intervention improved motivation in low-functioning patients with schizophrenia (Grant et al, 2012). This may indicate that similar strategies could be implemented in patients with 22q11.2DS to improve negative symptoms.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 96%
“…Although recent psychosocial treatments have shown efficacy in improving a subset of negative symptoms (Grant et al, 2012;Granholm et al, 2014;Grant et al, 2014), negative symptoms can often persist despite psychosocial treatments and antipsychotic medication (Tandon et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Collaborative development of imagery scripts with clients focusing on personal recovery goals could usefully augment existing thought-challenging approaches (Grant et al, 2012), subject to further controlled evaluation, faciliating engagement in meaningful and valued activity for this neglected group, and improving their quality of life. …”
Section: Resultsmentioning
confidence: 99%
“…Role playing future events (e.g. Grant et al, 2012); broadening present positive affect to apply to a vision of the future (e.g. Johnson et al, 2012); and guided positive imagery of a future activity (e.g.…”
Section: Psychological Models Of Negative Symptoms In Psychosismentioning
confidence: 99%